Awareness and adoption of a nurse sow management system among small-scale pig farmers in Nakuru County, Kenya - Osotsi, Joab Malanda; Gashew, Mequanint; Balogh, Péter; Novotni-Dankó, Gabriella (Acta Agraria Debreceniensis, 2024)
This study aimed to assess the level of awareness and adoption of nurse sow management strategies among small-scale pig farmers in Nakuru County, Kenya. The research included a survey of pig farmers who visited the Nakuru Agricultural Show in July 2023. A total of 139 farmers were interviewed within 5 days of the show. The corresponding author interviewed the respondents in a face-to-face engagement, where questions on nurse sow management were initially drafted in English and translated into Kiswahili, i.e. the second language in Kenya. The obtained results indicated that farmers came from two main regions of the county: the northern part (54.7%, 76/139) and the southern part (45.3%, 63/139). Levels of awareness and adoption were insignificant between the two groups (χ2, p